2017
DOI: 10.2147/copd.s131016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COPD patients initiating treatment with aclidinium or tiotropium in primary care in Catalonia: a population-based study

Abstract: ObjectiveTo describe and compare demographic and clinical profile of patients newly initiated on aclidinium (ACL) or tiotropium (TIO) and identify factors associated with newly initiated ACL in real-life clinical practice during 2013 in Catalonia.DesignWe performed a population-based, retrospective, observational study with data obtained from the Information System for Research Development in Primary Care, a population database that contains information of 5.8 million inhabitants (more than 80% of the Catalan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“… 32 In contrast, a large database study from Spain found higher levels of adherence: around 50% of patients newly initiated with LAMA therapy were persisting with their treatment after 9 months. 33 …”
Section: Discussionmentioning
confidence: 99%
“… 32 In contrast, a large database study from Spain found higher levels of adherence: around 50% of patients newly initiated with LAMA therapy were persisting with their treatment after 9 months. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Discontinuation rates used within the base case were based on data from the UPLIFT study [ 41 ], as it provides data over a 4-year follow-up, and this approach was validated by Spanish clinical experts [ 41 ]. Nevertheless, a sensitivity analysis was conducted using 50% discontinuation rates sourced from an observational study in Catalonia [ 55 ], and UMEC/VI remained dominant compared with TIO/OLO. Data on escalation to triple therapy from LAMA/LABA therapy are also not available from previous clinical studies, therefore it was necessary to make an assumption regarding the changes in FEV 1 once a patient escalated to subsequent triple therapy (LAMA/LABA+ICS).…”
Section: Discussionmentioning
confidence: 99%
“…One study only included individuals treated with aclidinium or tiotropium and observed an initially high persistence with LAMA that progressively decreased to 50% after 1 year of follow-up. 20 Izquierdo et al 21 conducted another population-based study in Castile-La Mancha (Spain) and observed a high rate of compliance (from 80 to 120%) in patients treated with LAMAs.…”
Section: Discussionmentioning
confidence: 99%